2018
DOI: 10.1161/jaha.117.007209
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin, Albuminuria, and Kidney Function in Cardiovascular Risk: The ARIC (Atherosclerosis Risk in Communities) Study

Abstract: BackgroundReduced estimated glomerular filtration rate (eGFR) and elevated urinary albumin‐to‐creatinine ratio (ACR) individually increase risk of cardiovascular disease (CVD). We hypothesized that these associations are stronger among people with abnormal (both low and high) hemoglobin levels.Methods and ResultsUsing 5801 participants with available hemoglobin measures of the ARIC (Atherosclerosis Risk in Community) study in 1996–1998, we explored the cross‐sectional association of eGFR and ACR with hemoglobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 36 publications
1
22
0
2
Order By: Relevance
“…The aetiology of anaemia is multifactorial, complex, and varies between patients. In HF, anaemia is considered to develop due to a complex interaction of iron deficiency, kidney disease and cytokine production, although micronutrient insufficiency and blood loss may also contribute [25,26]. All these factors are almost those associated with decreased serum albumin levels.…”
Section: Discussionmentioning
confidence: 99%
“…The aetiology of anaemia is multifactorial, complex, and varies between patients. In HF, anaemia is considered to develop due to a complex interaction of iron deficiency, kidney disease and cytokine production, although micronutrient insufficiency and blood loss may also contribute [25,26]. All these factors are almost those associated with decreased serum albumin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have examined the association of urine ACR with HF outcomes and in general, have shown that higher urine ACR is an independent risk factor for HF in general population-based cohorts (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). However, these studies had low representation of black individuals or relatively few HF events, limiting their ability to determine whether the association of ACR with HF differed by race.…”
Section: Discussionmentioning
confidence: 99%
“…Whether similar racial differences exist in the relationship between urinary albumin excretion and HF is unclear. Most prior studies examining the relationship between urinary albumin excretion and HF outcomes in general population-based cohorts had relatively low representation of black individuals (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), limiting their ability to determine if there is racial heterogeneity in the association of urinary albumin excretion with HF. Further, only a few studies assessed the association of urine albumin excretion with HF by different HF subtypes (preserved vs. reduced ejection fraction) (10,11,15).…”
Section: Introductionmentioning
confidence: 99%
“…Hematologic parameters from the CBC are used to screen for a variety of conditions ranging from anemia to infections to thrombocytopenia (2). Certain components, particularly white blood cell count (WBC), platelet count (PLT), and hemoglobin (HGB) are associated with a variety of chronic conditions, including cancer, kidney disease, and cardiovascular disease (36). The stability and analytic variability of these parameters can have implications for studies evaluating the association of these parameters with risk of clinical outcomes.…”
mentioning
confidence: 99%